Unravelling the impact of COVID-19 on mental health: A scoping review on traumatogenic events using the phases of response to disaster model - Hoof, Elke Van; Laet, Hannah De; Hochrath, Sophie; Philips, Evelien; Horczak, Paula; Cruyce, Nele Van den (Archives of Community Medicine and Public Health, 2021)
Background: Disease outbreaks such as the COVID-19 pandemic give rise to high levels of psychological distress in people worldwide. Since this is the first pandemic of its kind, the best available evidence is needed on what psychological needs could be expected during and after the pandemic. Objectives: In this scoping review existing research on traumatogenic events is examined in order to identify the potential impact on mental health of the COVID pandemic. The research findings are organized using the the phases of disaster response model. Results: A total of 34 longitudinal studies, 2 studies with multiple waves of data collection and 92 cross-sectional studies met the inclusion criteria. The studies included in this scoping review could be classified as: 87 studies on COVID-19, 2 on SARS, 19 on wars, 19 on terrorist attacks and 1 on a nuclear accident. Results indicate that stress, anxiety, depressive symptoms, insomnia, denial, anger, grief and fear can be anticipated as common reactions. The longer a pandemic continues, the higher the psychological strain is expected to be. Conclusions: The phases of response to disaster model offers a valid frame to unravel the impact of the pandemic on mental health over time. Specific attention must be given to vulnerable groups, whereby specific risk factors include age, gender, pre-existing mental health problems, healthcare profession, migration background, isolation and low socio economic status. However, these may change over time, and a delayed manifestation of psychosocial problems needs to be considered too. Mental health governance is, therefore, warranted throughout and even up to 6 months after the pandemic.